Metagenome Sequencing of the Prokaryotic Microbiota of the Hypersaline and Meromictic Soap Lake, Washington - Hawley, Erik R. (American Society for Microbiology, 2014)
Soap Lake is a small saline lake in central eastern Washington that is sharply stratified into two layers. In addition to being highly alkaline (~pH 10), Soap Lake also contains high concentrations of sulfide. Here, we report the community profile of the prokaryotic microbiota associated with Soap Lake surface water.